1989
DOI: 10.1111/j.1528-1157.1989.tb05453.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Effects of γ‐Vinyl GABA and Carbamazepine

Abstract: The effects of gamma-vinyl GABA (GVG) and carbamazepine (CBZ) monotherapy on somatosensory (SEP) and visual (VEP) evoked potentials and spectral quantitative EEG (QEEG) were studied in 17 patients with complex partial seizures using a cross-over double-blind study design. CBZ was associated with statistically significant prolongation of SEP latencies. When the drug was switched to GVG, shortening of the peak latencies was observed. Prolonged pattern-VEP peaks were observed both during CBZ and GVG monotherapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…However, VGB treatment had no effect on the EEG recordings from control rats (Supplemental Figures 4C and D) and did not suppress the slow waves of NREM sleep in these rats (Supplemental Figures 4B vs 4D). The latter results are in keeping with earlier studies that showed VGB has little or no effect on normal EEG activity in humans (Hammond and Wilder, 1985, Mervaala et al , 1989, Marciani et al , 1997). …”
Section: Resultssupporting
confidence: 93%
“…However, VGB treatment had no effect on the EEG recordings from control rats (Supplemental Figures 4C and D) and did not suppress the slow waves of NREM sleep in these rats (Supplemental Figures 4B vs 4D). The latter results are in keeping with earlier studies that showed VGB has little or no effect on normal EEG activity in humans (Hammond and Wilder, 1985, Mervaala et al , 1989, Marciani et al , 1997). …”
Section: Resultssupporting
confidence: 93%
“…For vigabatrin (VGB), the absence of cognitive side effects (compared with the existing first‐line drugs) is claimed, but the data come from only one center: Riekinnen et al in Finland (28,29), and are not based on high‐powered studies. A few additional studies did, however, not pass our aforementioned criteria, mostly because they were carried out in polytherapy designs.…”
Section: Newer Antiepileptic Drugsmentioning
confidence: 99%
“…Clinical and laboratory tests, including the serum concentrations of other antiepileptic drugs, were done at least every 3 months during the first 2 years of vigabatrin treatment and every 6 months thereafter. Electroencephalography Electroencephalograms (eight-, 16-, or 21-channel) that includ¬ ed photic stimulation and hyperventilation were evaluated before initiation of vigabatrin therapy; 7,12, and 24 months after the be¬ ginning of vigabatrin treatment; and when a patient was exclud¬ ed from the study. In addition to epileptiform activity, changes in the dominant occipital rhythm and the amounts of alpha, theta, and delta activities were assessed.…”
Section: Patients and Administration Of Vigabatrinmentioning
confidence: 99%